PELAKSANAAN KEGIATAN EKSTRAKULIKULER SEPAK BOLA MINI DI SDN 041/VI RANTANG PANJANG V KECAMATAN TABIR - Afdhol, Muhammad; Bani Pilitan, Raja (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract This research was carried out at SDN 041/VI Rantau Panjang V, Tabir District, which is one of the schools that rarely wins competitions. This is caused by several factors including facilities and infrastructure, student motivation, student interest and the lack of teacher professionalism. This research aims to find out an overview of the implementation of extracurricular mini football. In this research, the type of research is descriptive research. The population of students who are active in mini football extracurricular activities totaling 80 people. The sample was taken using a purposive stratified random sampling method of 40 people. The results of this research obtained from this research state that the description of the level of implementation of mini football extracurricular activities at SDN 041/VI Rantau Panjang V Tabir District is as follows: The level of achievement of student interest at SDN 041/VI is at a classification of 74.65% with good category. The level of achievement of facilities and infrastructure in the implementation of mini football extracurricular activities at SDN 041/VI Rantau Panjang V Tabir District is in the classification of 63.33% with the sufficient category. The level of achievement of the extracurricular activity process towards the implementation of extracurricular activities at SDN 041/VI Rantau Panjang V Tabir District is classified as 85.31% in the very good category. The level of professionalism achieved by teachers in the implementation of extracurricular activities at SDN 041/VI Rantau Panjang V Tabir District is classified as 81.5% in the good category. Keywords: Mini football Extrcurricular, Students SDN 041/VI